Curcumin ameliorates autoimmune diabetes. Evidences in accelerated murine models of type 1 diabetes - Castro, Carla Noemí (2014)
Type 1 diabetes (T1DM) is a T cell-mediated autoimmune disease that selectively destroys pancreatic β cells. The only possible cure for T1DM is to control autoimmunity against β cell-specific antigens. We explored whether the natural compound curcumin, with anti-oxidant and anti-inflammatory activities, might down-regulate the T cell response that destroys pancreatic β cells to improve disease outcome in autoimmune diabetes. We employed two accelerated autoimmune diabetes models: (i) cyclophosphamide (CYP) administration to non-obese diabetic (NOD) mice and (ii) adoptive transfer of diabetogenic splenocytes into NODscid mice. Curcumin treatment led to significant delay of disease onset, and in some instances prevented autoimmune diabetes by inhibiting pancreatic leucocyte infiltration and preserving insulin-expressing cells. To investigate the mechanisms of protection we studied the effect of curcumin on key immune cell populations involved in the pathogenesis of the disease. Curcumin modulates the T lymphocyte response impairing proliferation and interferon (IFN)-γ production through modulation of T-box expressed in T cells (T-bet), a key transcription factor for proinflammatory T helper type 1 (Th1) lymphocyte differentiation, both at the transcriptional and translational levels. Also, curcumin reduces nuclear factor (NF)-κB activation in T cell receptor (TCR)-stimulated NOD lymphocytes. In addition, curcumin impairs the T cell stimulatory function of dendritic cells with reduced secretion of proinflammatory cytokines and nitric oxide (NO) and low surface expression of co-stimulatory molecules, leading to an overall diminished antigen-presenting cell activity. These in-vitro effects correlated with ex-vivo analysis of cells obtained from curcumin-treated mice during the course of autoimmune diabetes. These findings reveal an effective therapeutic effect of curcumin in autoimmune diabetes by its actions on key immune cells responsible for β cell death.